Antibiotic Susceptibility Patterns among Indonesian Adults Hospitalized with Pneumonia - Akhmad, Afan Fatkhur; Ulfa, Maria; Azuma, Momoyo (Jurnal Respirasi, 2024)
Introduction: Pneumonia continues to be a global issue with significant morbidity and mortality rates. Increased multidrug-resistant (MDR) bacterial pneumonia, aging populations, chronically ill patients, and inadequate initial antibiotic therapy increase hospitalized pneumonia patients' morbidity and mortality. This study aimed to analyze the microbiological pattern and choose a therapy based on local antibiotic susceptibility patterns. Methods: From January 2020 to December 2022, a retrospective cross-sectional study was conducted on hospitalized pneumonia patients at Haji General Hospital, Surabaya, Indonesia. Data from medical records were gathered to illustrate patient features, bacterial culture, and antimicrobial susceptibility tests. This study included 172 patients. In this study, no specific statistical analysis was performed. The data were reported as a percentage (%).  Results: The patients were mostly 56-65 years old (36.6%) and male (55.2%). The most common comorbidities were cardiovascular disease (17.3%), and the others were diabetes mellitus (14.0%), cerebral vascular attack (CVA) (10.7%), and coronavirus infection (8.9%). Based on the sputum culture, the bacteria identified were Klebsiella pneumoniae (25.0%), Pseudomonas aeruginosa (20.9%), Acinetobacter baumannii (15.7%), and Escherichia coli (11.6%).  The most common bacteria isolated from sputum cultures was Klebsiella pneumoniae, which was more susceptible to amikacin and meropenem.  Conclusion: Only amikacin was an antibiotic susceptible to four primary pathogens. Rates of resistance to ciprofloxacin and ceftriaxone were high, and these empiric antibiotics should be used with caution in these patients.